2020
DOI: 10.1111/odi.13439
|View full text |Cite
|
Sign up to set email alerts
|

Is dental caries associated with liver transplantation? A systematic review and meta‐analysis

Abstract: Objective The aim of this systematic review and meta‐analysis was to evaluate the experience of dental caries in individuals pre‐ or postliver transplant. Materials and Methods Searches in PubMed, Scopus, Web of Science, Ovid, and Lilacs from databases’ inception date up to April 2020 were undertaken. Gray literature and manual searches were also conducted. Observational studies were eligible. The retrieved references were evaluated by two independent reviewers. Meta‐analysis and risk of bias assessment using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
(131 reference statements)
1
3
0
Order By: Relevance
“…Published research regarding dental caries experience in patients under transplantation therapy is controversial. Similar, low, and high DMF-T indices among pre-Tx and post-Tx groups have been reported [7,[10][11][12]25,31]. In the kidney group, our findings showed higher DMF-T scores in post-Tx.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Published research regarding dental caries experience in patients under transplantation therapy is controversial. Similar, low, and high DMF-T indices among pre-Tx and post-Tx groups have been reported [7,[10][11][12]25,31]. In the kidney group, our findings showed higher DMF-T scores in post-Tx.…”
Section: Discussionsupporting
confidence: 89%
“…In a previous study [12] developed with SOT (heart, liver, and kidney) patients, mean DMF-T pre-transplantation (18.1 ± 5.3) and posttransplantation (16.8 ± 8.3) showed similarity with our findings. Several studies reported poor habits of oral hygiene and poor oral health status among adults under transplantation therapy [11,25,[30][31][32]. Factors, such as modifications in lifestyle, usage of medicines that reduce salivary flow, and the high burden of ESKD and chronic liver disease in pre-Tx candidates, seem to reduce dental care priorities in this population, increasing the development of caries lesions [32].…”
Section: Discussionmentioning
confidence: 99%
“…Though liver transplantation (LTx), the treatment of end-stage liver conditions was found relevant with increased risk for dental caries in both pre-LTx and post-LTx populations, patients at the pre-LTx stage showed no signi cant increase in the total amount of UDC. (39) Together with the increasing knowledge of microbiota emerged the therory of oral-gut-liver axis. Its unbalance is speculated to trigger liver in ammation and dysregulated immune response, though most evidence is based on periodontal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Formal dental evaluation (and extractions where necessary) are therefore recommended as part of the liver transplantation work up 39 . The prevalence of periodontal disease in this group is reported to be as high as 75% 40 …”
Section: Case 2: Dental Extractions and Risk Of Bleedingmentioning
confidence: 99%